Effects of an eccentric overload and small-side games training in match accelerations and decelerations performance in female under-23 soccer players - Nevado-Garrosa, F.; Torreblanca-Martínez, V.; Paredes-Hernández, V.; Balsalobre-Fernández, C. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aims of this study were: 1) to investigate the impacts that an eccentric overload training (EOT) and a small-side game training (SSGT) have on the characteristics of the accelerations (ACC) and decelerations (DCC) of the players in a soccer match; and 2) to determine if EOT and SSGT could affect the ACC and DCC reduction over time in a soccer match. METHODS: Twenty-three female soccer players from a Spanish professional club were split into three groups: a small-sided game training group (SGG), an eccentric overload training group (EOG) and a control group (CG). RESULTS: The SSG improved the high intensity distance performed (ES [CI]=0.72 [0.22; 1.22]), the number of high intensity actions (ES [CI]=0.65 [0.01; 1.29]), the percentage of repeated high intensity actions (ES [CI]=0.54 [-0.17; 1.25]), the initial velocity of the ACC (ES [CI]=0.55 [-0.08; 1.17]) and the percentage of repeated accelerations (ES [CI]=0.87 [-0.18; 1.91]) with respect to the control group. The EOG obtained better results in distance travelling accelerating (ES [CI]=0.84 [0.09; 1.60]) and decelerating (ES [CI]=0.87 [0.23; 1.51]) above 3 m/s2, maximum ACC (ES [CI]=1.92 [0.90; 2.94]) and DCC (ES [CI]=1.29 [0.44; 2.14]) and the average of maximum ACC (ES [CI]=0.89 [0.23; 1.54]) and DCC (ES [CI]=1.08 [0.62; 1.55]) with respect to the CG. A decrement in the ACC and DCC performance was observed between the first and last 15 minutes of the competition, except for the EOG. CONCLUSIONS: The SSG obtained mainly improvements in variables related with efforts repetitions and the capacity of maintaining the ACC and the DCC over time, while improvements in the EOG were related to intensity in the ACC and DCC.